Writing Instructional Objectives - R. Kirby Barrick; Andrew C. Thoron (EDIS)
Good teaching begins with well-written instructional objectives. Instructional objectives identify the knowledge, skills, and abilities that students will possess upon successfully learning the material. This 4-page fact sheet outlines the three types of objectives (cognitive, psychomotor, and affective) as well as the different components of objectives (condition, performance, criterion). A well-written instructional objective will lead to clear teaching and ultimately, student success. Written by R. Kirby Barrick and Andrew C. Thoron, and published by the Agricultural Education and Communication Department, January 2016.